Philippine medical thesaurus on anatomy body regions in Kapampangan - Lising, Jeffrey O. (2004)
Effective care and management of a patient is attained with good patient doctor relationship. Proper management comes with proper diagnosis. Diseases are often misdiagnosed because of miscommunication due to language differences between the doctor and the patient. Communication barrier between them has been one of the major constraints in better disease management. However, there are no books currently available to translate standard medical terms into Filipino or other Philippine dialects.